(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction:In the present sphere, aesthetics and beauty is a major worry for many people, in the field of dentistry.Beauty of gingiva is one of the main factors to be considered in success of restorative dental care.Black triangle is the result of interdental papilla deficiency.. The majorcomplaints by the patients of black triangle areaesthetic problems, phonetic problems, food impaction, oral hygiene maintenance problems. One of the major difficult task is to overcome and correct interdental papillary deficiency.Etiological factors related to interdental papillary deficiency are periodontal disease, loss of the interdental bone related to the concerned papilla, length of embrasure area, angulation of root, location of contact points interproximally. Objective:This review article attempts to present an overview on the various treatment modalities in management of black triangle. Discussion and Conclusion: An interdisciplinary approach by the periodontist, orthodontist, prosthodontist and restorative dentist may be required for the management and correction of this soft tissue defect. It is essential if a predictable clinical results is to be achieved. Before starting the treatment patient should be made aware about the etiology and all the treatment alternatives. An esthetic regeneration of the interdental papilla can be gained by maintaining the height of interdental papilla.